A festa religiosa de Nossa Senhora da Conceição de Vila Viçosa ao tempo de D. João II, duque de Bragança (1630-1640) - Pegacha Pardal, Francisco José (História: revista da Faculdade de Letras da Universidade do Porto, 2021)
Resumo: A devoção à Imaculada Conceição em Vila Viçosa remonta à Idade Média. Com o estabelecimento da Casa de Bragança na localidade, a mesma foi muito estimada pela família ducal. A festa, organizada pela Confraria de Nossa Senhora da Conceição, tinha o momento alto na procissão, que contava com a participação do povo e das elites, nomeadamente o duque D. João II e seus familiares. Palavras chave: Imaculada Conceição. Festa Religiosa. Vila Viçosa. Casa de Bragança. Idade Moderna. Abstract: The devotion to the Immaculate Conception in Vila Viçosa reassembles to the Middle Age. With the establishment of House of Braganza in the locality, was extremely estimated by the ducal family. The party, organized by the Brotherhood of Our Lady of Conception, had a hight moment in the procession, which had not only the participation of the commonwealth and the elites, but also the participation of the duke John II and his family. Key words: Immaculate Conception. Religious Party. Vila Viçosa. House of Braganza. Modern Age. Résumé: La dévotion à l’Immaculée Conception à Vila Viçosa remonte au Moyen Âge. Avec l’établissement de la Maison de Bragance dans la localité, il a été grandement estimé par la famille ducale. La fête, organisé par la Confrérie Notre-Dame de la Conception, a eu le grand moment dans la procession, qui a eu la participation du peuple et des élites, à savoir le duc Jean II et sa famille. Mots-clés: Immaculée Conception. Fête Religieuse. Vila Viçosa. Maison de Bragance. Époque Moderne. Resumen: La devoción a la Inmaculada Concepción en Vila Viçosa se remonta a la Edad Media. Con el establecimiento de la Casa de Braganza en la localidad, fue muy apreciada por la familia ducal. La fiesta, organizada por la Confradía de Nuestra Señora de la Concepción, tuvo el momento alto en la procesión, que contó con la participación del pueblo y las élites, a saber, el duque Juan II e sus familiares. Palabras clave: Inmaculada Concepción. Fiesta Religiosa. Vila Viçoca. Casa de Braganza. Edad Moderna.